Statistical optimalization of α-Amylase production from Penicillium notatum NCIM 923 and kinetics study of the purified enzyme - Ghosh, Priyanka; Das, Arpan; Gayen, Soumi; Mondal, Keshab Chandra; Ghosh, Uma (Acta Biologica Szegediensis, 2015)
In this study, response surface methodology (RSM) was employed to optimize the production of α-amylase by Penicillium notatum NCIM 923 through solid-state fermentation. The individual and combinational effects of the factors, i.e. substrate amount, initial moisture, fermentation time, temperature and size of inoculum were found to have significant effects on α-amylase production: the optimum values of the tested variables were 5 g, 70%, 94 h, 28 °C and 20%, respectively. The predicted amylase production (2819.24 U/g) was in good agreement with the value measured under optimized surrounding (2810.33 U/g). The molecular mass of purified α-amylase was about 52 kDa. The enzyme activity exhibited its pH optimum between pH 4.6 and 6.6, and it had maximal activity at 50 °C. The apparent Km and Vmax of α-amylase for starch were 4.1 mg/ml and 247.6 μmol/min, respectively. The activation energy (Ea) for starch hydrolysis was found to be 14.133 kJ/mol. The enzyme was thermostable with half-life (t1/2) of 110 min at 80 °C and temperature coefficient (Q10) value of 1.0. Purified enzyme was activated by Ca2+ and inhibited by Hg2+ ions. EDTA also inhibited the enzyme activity, indicating that the purified enzyme is a metalloenzyme.